PENERAPAN TEKNOLOGI IOT UNTUK SISTEM PERINGATAN DINI GEMPA DENGAN NOTIFIKASI TELEGRAM DAN BLYNK - Suni, Guido Adolfus; Kavin Balol, Lambano (Jurnal Komputer dan Teknologi, 2026)
In recent years, earthquakes have become one of the most frequent natural disasters in Indonesia. Unfortunately, the existing earthquake early warning system is still centralized and has not effectively reached the household scale. This study aims to design and implement an Internet of Things (IoT)-based earthquake early warning system by utilizing the SW-420 vibration sensor and the NodeMCU 8266 microcontroller. This system is designed to be able to detect vibrations in real-time and provide automatic notifications via the Telegram and Bylnk applications to users. The research method used is the engineering research method with a descriptive approach including the stages of hardware design, software programming, and system testing. The implementation results show that the system is able to detect vibrations accurately with an average response rate of less than one second, and successfully sends real-time notifications to users via Telegram and Bylnk. Thus, this system can be used as an alternative solution for simple earthquake early warning that is effective, economical, and easy to implement in the home environment.